Analisis Kinerja Keuangan Pada PT Sinar Mas Agro Resources And Technology Tbk - Dimas Try Handoko; Masnoni; Irsan; Hilwa Anggraini; Zein Ghozali (JURNAL EKOBIS Kajian Ekonomi dan Bisnis, 2022)
The purpose of this study was to determine the financial performance of PT Sinar Mas Agro Resources and Technology Tbk using Liquidity Ratio Analysis and Solvability Ratios. The data used in this study is secondary data, namely data obtained from idx.co.id and the official website of PT Sinar Mas Agro Resources and Technology Tbk. The data is in the form of documents consisting of statements of financial position from 2017 to 2019 and company history. The analytical method used is data analysis using financial ratios, namely theanalysis of liquidity ratios and solvency ratios. The results of this study indicate that the liquidity ratio seen from the current ratio, quickratio and cash ratio, as well as the solvency ratio seen from the debt to total assets ratio and debt to equity ratio are in the bad category.